PGS Post - Volume 1, Issue 1, May 2023 - UiTM, IPSis (Institut Pengajian Siswazah (IPSis), 2023)
Greetings and welcome to the inaugural edition of the Postgraduate Post for the year 2023! As we begin a new academic year, IPSis is proud to continue our mission of providing outstanding services to our postgraduate students and the university. We are thrilled to announce that our enrollment has continued to grow, with a 10% increase in overall enrollment and a particularly strong increase in our international student population. This growth reflects the high demand for our academic programs and the exceptional reputation of UiTM.